Life prediction analysis of patrol vessel made from FRP with variations of wave height and wave direction - Octaviano Noel; Zubaydi Achmad; Ismail Abdi; Ariesta Rizky Chandra; Pratikno Herman; Rahmana Putra Nicky; Triputrastyo Murwatono Totok (BIO Web of Conferences)
The Fiber Reinforced Plastic (FRP) material used in ships has advantages such as lighter weight, resistance to corrosion, and lower maintenance costs. However, transitioning from materials like steel and aluminum, commonly used in production, requires knowledge of the lifetime of FRP as a ship structure, allowing for an estimation of how long the ship can operate. Additionally, predicting the ship’s lifetime is also necessary to meet ship safety factors. This study employs numerical testing using the Finite Element Method to predict lifetime of patrol boats in Bangka Belitung waters. Wave height variations (0.5-2 meters) and wave direction (following sea, head sea, and beam sea) are considered at a constant speed of 22 knots. Fatigue life calculation is done by determining the bending moment load at various wave heights. The bending moment is in an Ansys static structural analysis to calculate stress and deformation. The highest stress occurs in the stern frame with the value of 18.347 MPa while the lowet is in the bow frame with the value of 16.682 MPa. By calculating the stress on each variation, the life prediction can be calculated. The life prediction of a patrol vessel is 32 years and 8 months.